Zoonotic pathogens in the food chain - Krause, D. O; Hendrick, S (Zoonotic pathogens in the food chain, 2011)
Beginning with their sources, including manure and animal feed, and detailing their development, spread and transmission to humans, Zoonotic Pathogens in the Food Chain gives an insightful introduction to and epidemiological overview of the problems raised by zoonotic pathogens. The authors specifically examine the attributes of microorganisms that allow potential contamination of food sources and the factors in modern animal production processes that contribute to the risk of infection. Chapters discuss in detail pathogens that have recently emerged as important sources of infection, investigating in depth the implications of avian flu, swine flu, bovine spongiform encephalopathies and Johne's disease for human consumers, and considering where potential mitigation strategies should be focused. With a focus on new trends in animal production, such as organic livestock farming and raw milk consumption, this text provides an interesting and up-to-date reference for researchers, academics and those with an interest in pathology working in the livestock industry.